She is incorrect cause if we take the number 20 and take 25% of it it equals 5 so now 20 is only 15. They if we take 75% away from 20 is equals 15 so then we only have 5 from 20 left. Therefore she’s incorrect because 75% leaves 5/20 and 25% leaves 15/20. Hope that makes sense.
The denominator is 24 in the fraction
Answer:
Option (b) is correct.
![(2^\frac{1}{4} )^4=2^\frac{1}{4} \times 2^\frac{1}{4}\times 2^\frac{1}{4}\times 2^\frac{1}{4}=2^{(\frac{1}{4}+ \frac{1}{4}+ \frac{1}{4}+ \frac{1}{4} )}=2^{1}=2](https://tex.z-dn.net/?f=%282%5E%5Cfrac%7B1%7D%7B4%7D%20%29%5E4%3D2%5E%5Cfrac%7B1%7D%7B4%7D%20%5Ctimes%202%5E%5Cfrac%7B1%7D%7B4%7D%5Ctimes%202%5E%5Cfrac%7B1%7D%7B4%7D%5Ctimes%202%5E%5Cfrac%7B1%7D%7B4%7D%3D2%5E%7B%28%5Cfrac%7B1%7D%7B4%7D%2B%20%5Cfrac%7B1%7D%7B4%7D%2B%20%5Cfrac%7B1%7D%7B4%7D%2B%20%5Cfrac%7B1%7D%7B4%7D%20%29%7D%3D2%5E%7B1%7D%3D2)
Step-by-step explanation:
Given: ![(2^\frac{1}{4} )^4](https://tex.z-dn.net/?f=%282%5E%5Cfrac%7B1%7D%7B4%7D%20%29%5E4)
We have too choose the correct simplification for the given statement.
Consider ![(2^\frac{1}{4} )^4](https://tex.z-dn.net/?f=%282%5E%5Cfrac%7B1%7D%7B4%7D%20%29%5E4)
Using property of exponents,
We have,
![(2^\frac{1}{4} )^4=2^\frac{1}{4} \times 2^\frac{1}{4}\times 2^\frac{1}{4}\times 2^\frac{1}{4}](https://tex.z-dn.net/?f=%282%5E%5Cfrac%7B1%7D%7B4%7D%20%29%5E4%3D2%5E%5Cfrac%7B1%7D%7B4%7D%20%5Ctimes%202%5E%5Cfrac%7B1%7D%7B4%7D%5Ctimes%202%5E%5Cfrac%7B1%7D%7B4%7D%5Ctimes%202%5E%5Cfrac%7B1%7D%7B4%7D)
Again applying property of exponents ![a^m\times a^m=a^{n+m}](https://tex.z-dn.net/?f=a%5Em%5Ctimes%20a%5Em%3Da%5E%7Bn%2Bm%7D)
We have,
![(2^\frac{1}{4} )^4=2^{(\frac{1}{4}+ \frac{1}{4}+ \frac{1}{4}+ \frac{1}{4} )}](https://tex.z-dn.net/?f=%282%5E%5Cfrac%7B1%7D%7B4%7D%20%29%5E4%3D2%5E%7B%28%5Cfrac%7B1%7D%7B4%7D%2B%20%5Cfrac%7B1%7D%7B4%7D%2B%20%5Cfrac%7B1%7D%7B4%7D%2B%20%5Cfrac%7B1%7D%7B4%7D%20%29%7D)
Simplify, we have,
![(2^\frac{1}{4} )^4=2^{\frac{4}{4}}](https://tex.z-dn.net/?f=%282%5E%5Cfrac%7B1%7D%7B4%7D%20%29%5E4%3D2%5E%7B%5Cfrac%7B4%7D%7B4%7D%7D)
we get,
![(2^\frac{1}{4} )^4=2^{1}=2](https://tex.z-dn.net/?f=%282%5E%5Cfrac%7B1%7D%7B4%7D%20%29%5E4%3D2%5E%7B1%7D%3D2)
Thus, ![(2^\frac{1}{4} )^4=2](https://tex.z-dn.net/?f=%282%5E%5Cfrac%7B1%7D%7B4%7D%20%29%5E4%3D2)
Option (b) is correct.
Answer:
2x^2-12x-54
Step-by-step explanation:
First 2x times x along with 2x times -9
Second 6 times x along with 6 times -9
2x^2-18x+6x-54
=2x^2-12x-54
Answer:
it's C
Step-by-step explanation:
I think I don't know I just guessed